2013
DOI: 10.5194/nhess-13-1313-2013
|View full text |Cite
|
Sign up to set email alerts
|

Some comments on the potential seismogenic origin of magnetic disturbances observed by Di Lorenzo et al. (2011) close to the time of the 6 April 2009 L'Aquila earthquake

Abstract: In this paper we provide comments about the potential seismogenic origin of magnetic disturbances that Di Lorenzo et al. (2011) observed from few minutes before to about one hour after the 6 April 2009 L'Aquila earthquake. The coincidence with the earthquake induced the authors to think that the observed magnetic signals were linked to the main phase of the seismic event. Here, we will discuss the unusual polarization in the XZ plane of the magnetic disturbances observed by Di Lorenzo et al. (20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Thus, some researchers do not agree that magnetic changes observed prior to earthquakes had seismogenic origin. They have demonstrated that many published preearthquake ULF magnetic changes [see Campbell , ; Masci , , , , , , , ; Masci and De Luca , ; Masci and Thomas , , , ; Moldovan et al ., ; Romanova et al ., ; Thomas et al ., , ] and ionospheric disturbances [see Foppiano et al ., ; Masci , , ; Masci and Thomas , , ; Masci et al ., ; Thomas et al ., , ] are reasonably related to instrumentation malfunction, to the analysis procedure, or to the normal geomagnetic activity in response to Sun‐Earth interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some researchers do not agree that magnetic changes observed prior to earthquakes had seismogenic origin. They have demonstrated that many published preearthquake ULF magnetic changes [see Campbell , ; Masci , , , , , , , ; Masci and De Luca , ; Masci and Thomas , , , ; Moldovan et al ., ; Romanova et al ., ; Thomas et al ., , ] and ionospheric disturbances [see Foppiano et al ., ; Masci , , ; Masci and Thomas , , ; Masci et al ., ; Thomas et al ., , ] are reasonably related to instrumentation malfunction, to the analysis procedure, or to the normal geomagnetic activity in response to Sun‐Earth interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Because the Earth's crust is fluid saturated, Dahlgren et al (2014) conclude that significant electric currents are not expected to be generated the days before earthquakes during the slow stress accumulation in the region of earthquake nucleation; as a consequence no electric and magnetic signals are expected to be observed on the Earth's surface. However, note that studies of data records from L'Aquila area (see Biagi et al, 2010;Masci, 2012b;Masci and Di Persio, 2012;Masci and De Luca, 2013;Villante et al, 2010) have identified no anomalous magnetic or electric effects during days to hours before and after the 6 April earthquake that might be hypothesized to have seismogenic origin. Still, in a recent report, Masci and Thomas (2016), by investigating magnetic field measurements from multiple magnetometers and seismic and strong motion records close to the earthquake epicentre, have shown that there is no evidence that might support the generation of an underground electric Nat.…”
Section: On the Hypothesized Generation Mechanismsmentioning
confidence: 95%
“…No actual coseismic electric and magnetic effects in correspondence to the 6 April main shock have been yet identified, and reported magnetic changes claimed to be related to this earthquake have been shown not to be seismogenic Masci and De Luca, 2013].…”
Section: The 6 April 2009 L'aquila Earthquakementioning
confidence: 95%
“…Studies using data from L'Aquila area, instead, did not identify magnetic changes that can be actually put in relation with the 6 April earthquake [see, e.g., Masci and Di Persio , ; Villante et al , ]. No actual coseismic electric and magnetic effects in correspondence to the 6 April main shock have been yet identified, and reported magnetic changes claimed to be related to this earthquake have been shown not to be seismogenic [ Masci , ; Masci and De Luca , ].…”
Section: The 6 April 2009 L'aquila Earthquakementioning
confidence: 99%
See 1 more Smart Citation